Intranasal insulin influences the olfactory performance of patients with smell loss, dependent on the body mass index: A pilot study - Schoepf, V.; Kollndorfer, Kathrin; Pollak, M.; Mueller, C. A.; Freiherr, Jessica (Rhinology, 2015)
Background: The application of intranasal insulin in healthy humans has been linked to improved memory function, reduced food intake, and increased olfactory thresholds, There has also been some correlation between the morbidities associated with central nervous system (CNS) insulin resistance, such as type II diabetes mellitus, Alzheimer's disease, obesity, and impaired odour recognition. Given that impaired odour recognition is an important component of olfactory performance, mechanisms that govern these effects may account for impaired olfactory functions in anosmic patients.Methodology:Ten patients with post-infectious olfactory loss received intranasal administration of 40 IU insulin or a placebo solution, as well as olfactory performance tests before and after administration.Results: When administered insulin, patients exhibited an immediate performance improvement with regard to olfactory sensitivity and olfactory intensity ratings. In addition, more odours were correctly identified. Furthermore, an improvement in the odour identification task was detected in patients with higher body mass index.Conclusion: Results of this pilot study shed light on the link between cerebral insulin level and an impaired sense of smell.This research line might provide a better understanding of olfactory loss in relation to eating and dietary behavior, and could offer opportunities to develop faster therapeutic intervention for patients with olfactory dysfunction.
Keywords: anosmia; olfactory dysfunction; metabolic influence; intranasal insulin; smell; olfaction